Allocation of humanitarian aid after a weather disaster. (June 2023) - Mogge, Lukas; McDonald, Morag; Knoth, Christian; Teickner, Henning; Purevtseren, Myagmartseren; Pebesma, Edzer; Kraehnert, Kati
Highlights: Need is a strong predictor for the allocation of international humanitarian aid in Mongolia during a natural disaster. The allocation of governmental humanitarian aid is also driven by need, though to a lesser extent. Neither political alignment nor core voter considerations affect the allocation of humanitarian aid. Abstract: This paper tests whether need or political economy factors determine the allocation of humanitarian aid in the wake of the 2015/16 winter disaster in Mongolia. The identification strategy exploits the exogenous nature of the extremely cold, snowy winter and its spatial variation across Mongolia as well as the fact that the Government defined clear criteria of need across districts based on meteorological risk projections. Using rich district-level data, we distinguish between humanitarian aid delivered by the Mongolian Government and by international donors at the extensive margin (whether a district received any aid) and intensive margin (targeted households per district). Results show that projected need is the strongest predictor for the allocation of international humanitarian aid across districts. Projected need is less relevant for the allocation of governmental humanitarian aid. We do not find evidence that political alignment or core voter considerations matter for either governmental or international humanitarian aid in this young democracy.